Comparative evaluation of the antioxidant capacity of ferulic acid and synthesized propionyl ferulate - Oluyomi Stephen Adeyemi, Ayonote Divine Ayebakuro, Oluwakemi Josephine Awakan, Olubunmi Atolani, Opeyemi Adejumo, Adewole Ibrahim, Damilare Rotimi, Gaber El-Saber Batiha, John Olusegun Ojediran (Journal of Applied Pharmaceutical Science, 2020)
Ferulic acid (FA) is a polyphenolic compound with demonstrated antioxidant capacity. In this study, propionyl ferulate (PF) was synthesized and characterized using melting point, ultraviolet spectroscopy, Fourier-transform infrared spectroscopy, and mass spectrometry. The propionyl ferulate was comparatively evaluated for antioxidant potential which included the ability to quench reactive species of 2,2-diphenyl-2-picrazyl-hydrazyl (DPPH), hydroxyl, nitric oxide, and superoxide anion. In addition, the total antioxidant capacity and membrane stabilizing properties of the ferulate were determined. Comparatively, the spectroscopically characterized PF showed superior scavenging capacity for the DPPH, hydroxyl, and nitric oxide free radicals when compared to FA. On the contrary, PF showed a poor scavenging capacity for superoxide anion radicals. Furthermore, PF showed little or no potential for membrane stability. In conclusion, the data suggest that structurally modifying FA to PF improved the antioxidant capacity for several free radicals.
Keywords: Antioxidants, food additives, medicinal chemistry, medicinal biochemistry, natural products.